(Over)determining social disorder: Tajikistan and the economic collapse of perestroika. Issue 3 (2nd July 2016) - Scarborough, Isaac
ABSTRACT: This article analyses the rise of social unrest in the Tajik SSR in 1990–1991 from the perspective of the republic's place within the broader Soviet economy and the collapse of that economy over the course of perestroika (1985–1991). Countering standard narratives of glasnost, democratization and nationalism in Tajikistan, it demonstrates that a close reading of the historical record points to sharp economic downturn as the most plausible immediate cause of the social disorder that came to engulf the Tajik SSR in the final years of the USSR and led to the Tajik Civil War of the 1990s.